STUDY QUR'AN: The Quarantine Program for Memorizing the Qur'an Effectively at Madrasatul Qur'an Islamic Pesantren Mambaul Falah Tambilung Tambak Bawean Gresik - Ahmad Halid (Universitas Darussalam Gontor, 2023)
This article explains the quarantine program for quickly memorizing the Qur’an. Because students are motivated to memorize quickly, this quarantine program is exciting. This study examines how the Qur’an Memorizing Quarantine Program at Madrasatul Qur’an Islamic boarding school Mambaul Falah Tambilung Tambak Bawean Gresik can help students memorize the Qur’an in a relatively short period. Using qualitative, descriptive data sources such as observation and interviews, Miles and Huberman analysis, and source triangulation to ensure data validity. The findings of this study indicate that the Koran memorization quarantine program is highly effective because students are solely focused on memorizing the Koran and are constantly guided by ustadz with core and companion or supporting programs.